Samotny smakosz albo krótki przewodnik po komiksowych przedstawieniach konsumpcji - Michał Traczyk (Załącznik Kulturoznawczy)
Depictions of food consumption in comic books are quite numerous but they rarely stick in the minds of readers, especially when they serve as the background for the unfolding story. If the authors, however, decide to depict food, they do so in large part to achieve a few specific purposes: emphasize the characteristics of the characters, deconstruct the seriousness of the narrative, and introduce humorous elements. All of this takes place on two levels: aesthetic (from realistic to cartoonish) and existential (eating is one of the most ordinary day-to-day activities). The article aims to show the various possibilities of using representations of food consumption and discuss their meaning using selected examples.